Study on radiation resistence of permanent NdFeB-base magnets under continuons radiation conditions - Dovbnya, A.N.; Tolstoy, A.E.; Bovda, A.M.; Utva, O.M.; Uvarov, V.L.; Krasnogolovets, M.A. (Вопросы атомной науки и техники, 1999)
The development of present-day technologies and materials for creating permanent magnets (in particular, at NSC KIPT), and increasing demands for devices in which these materials are used for physics and technology of intense (10 to 40 MeV) electron beam forming have motivated the comprehensive study on characteristics of these materials under extreme conditions of their use.